Mushrooms arising from mole latrines reveal the life of moles: proposals of “myco-talpology” and “habitat-cleaning symbiosis” - N. Sagara; N. Tuno; Y. Fukasawa; S. Kawada; T. Kasuya (The European Zoological Journal)
Myco-talpology is the study of the ecological relationship between moles and mushrooms. This discipline emerged from our 1976 discovery that the underground nests of talpid moles can be identified by the aboveground fruiting of the agarics Hebeloma sagarae, a Japanese sibling species of the European Hebeloma radicosum, or Hebeloma danicum. These fungi colonize mole latrines near nests, forming ectomycorrhizal associations with the roots of host trees. Through this process, fungal hyphae and plant roots absorb, transform and translocate nutrients from mole excretions, effectively cleaning the mole’s habitat. The mushrooms emerge from the ground with thick, root-like tissue extending from the ectomycorrhizae. The presence of these fruit-bodies serves as the sole indicator of underground mole nests, offering novel insights into mole ecology. We excavated 74 H. sagarae or H. danicum sites in Japan and 13 H. radicosum sites in Europe, identifying the associated animal species. These investigations provided new perspectives on latrine locating, nest structures, breeding behaviours, nestling presence, the coexistence of different Talpini species and the persistence of long-term nesting at the same sites accompanying changes in inhabitants. Furthermore, our findings suggest the existence of a tripartite habitat-cleaning symbiosis involving moles, mushrooms and host trees, a relationship that has likely persisted in Japanese and European forests for an extended period. Although moles are traditionally considered inhabitants of open areas, their specialized association with mushrooms and trees suggests they may have originally evolved as forest inhabitants.